Inhibition of Arterial Thrombosis by a Soluble Tissue Factor Mutant and Active Site-blocked Factors IXa and Xa in the Guinea Pig - Himber, Jacques; Refino, Canio J.; Burcklen, Louis; Roux, Sébastien; Kirchhofer, Daniel (Thrombosis and Haemostasis, 2001)
The substrate recognition region of tissue factor contains two residues, Lys165 and Lys166, which are important for macromolecular substrate activation by the tissue factor:factor VIIa complex. Replacement of these two residues with alanine in a soluble version of human tissue factor resulted in a mutant, hTFAA, which can bind factor VIIa but forms an enzymatically inactive complex. We found that hTFAA inhibits the activity of guinea pig factor VIIa, allowing us to evaluate hTFAAs effects on thrombosis and hemostasis in a guinea pig model of recurrent arterial thrombosis. In addition to heparin, the effects of hTFAA were compared to active site inhibited factor IXa (F.IXai) and factor Xa (F.Xai). We found that hTFAA, F.IXai and F.Xai were potent antithrombotics and may possess a decreased risk of hemorrhage when compared to unfractionated heparin. When administered at a dose that inhibited thrombosis by about 90%, hTFAA neither affected cuticle bleeding nor the activated partial thromboplastin time, and had only a modest effect on the prothrombin time. At equi-efficacious doses, F.IXai, F.Xai and heparin prolonged bleeding times by 20% (p >0.5), 50% (p <0.05) and 100% (p <0.01), respectively. In summary, our study demonstrates that, unlike heparin, specific inhibitors of factors VIIa, IXa and Xa can produce antithrombotic effects without or with only minimally disturbing normal hemostasis. The results further suggest that factor VIIa and factor IXa are especially promising targets for antithrombotic drug development.
Keywords: Tissue factor; factor IX; factor X; factor VII; anticoagulants; thrombosis